2017
DOI: 10.1080/20002297.2017.1337477
|View full text |Cite
|
Sign up to set email alerts
|

Effect of erythritol on microbial ecology of in vitro gingivitis biofilms

Abstract: Gingivitis is one of the most common oral infections in humans. While sugar alcohols such as erythritol are suggested to have caries-preventive properties, it may also have beneficial effects in prevention of gingivitis by preventing maturation of oral biofilms. The aim of this study was to assess the effect of erythritol on the microbial ecology and the gingivitis phenotype of oral microcosms. Biofilms were inoculated with stimulated saliva from 20 healthy donors and grown in a gingivitis model in the continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…A recent randomized clinical trial has demonstrated the effectiveness of this powder in removing dental plaque during repeated instrumentation of residual pockets in supportive periodontal therapy ( 12 ). To summarize, erythritol seems to induce a change in the oral microbiota, shifting it towards a more favorable environment where the traditional colonizers are predominant ( 32 ). One possible explanation for these positive outcomes might be related to the attachment of erythritol/chlorhexidine particles to the dental implants.…”
Section: Discussionmentioning
confidence: 99%
“…A recent randomized clinical trial has demonstrated the effectiveness of this powder in removing dental plaque during repeated instrumentation of residual pockets in supportive periodontal therapy ( 12 ). To summarize, erythritol seems to induce a change in the oral microbiota, shifting it towards a more favorable environment where the traditional colonizers are predominant ( 32 ). One possible explanation for these positive outcomes might be related to the attachment of erythritol/chlorhexidine particles to the dental implants.…”
Section: Discussionmentioning
confidence: 99%
“…Harmful changes in oral microbiota balance (dysbiosis) can lead to dental caries, periodontal disease, and various systemic diseases, including cardiovascular disease, rheumatoid arthritis, colorectal cancer, pneumonia, and diabetes [5,6,8,43]. In order to elucidate the nature of oral ecosystems, several studies have been conducted to investigate the response of oral microbiota using environmental factors, such as nitrate, erythritol, and arginine [44,45,46]. In this study, we investigated the effect of NO, which is known to occur in the oral cavity and is one of the environmental factors that may shift the oral microbiota, on dental plaque using a simple system for in vitro culture.…”
Section: Discussionmentioning
confidence: 99%
“…Erythritol is a naturally occurring sugar alcohol that is approved as a sugar substitute with no or minimal laxative effect and without any quantity restriction as a food additive. In various in vitro and clinical studies, erythritol showed an inhibitory effect on biofilm formation, on the presence of caries-inducing bacteria, and on the susceptibility of subjects to caries [3][4][5]. Xylitol, also a naturally occurring sugar alcohol, is currently used mainly as a sugar substitute because it has no or minimal acidogenic potential.…”
Section: Introductionmentioning
confidence: 99%